(untitled) (Scientific journal of the Fergana State University, 2023)
This article explores practical assignments that develop students’ vocabulary by teaching vocabulary in a variety of contexts. It is recommended that these assignments be applied to native language textbooks. One of the most important indicators of a student’s speech is his or her vocabulary. The article describes the results of practical exercises for children aged 7 to 15 years. According to the results, according to the current state educational standard for mother tongue education, three factors: creativity, independent thinking, the product of thought in accordance with the speech situation in oral and written forms correctly, fluently the importance of achieving the formation and development of expressive skills has been proven.